Genome-wide comparative and evolutionary analysis of transposable elements in eight different legume plants - Jayaswal, Pawan Kumar; Shanker, Asheesh; Singh, Nagendra Kumar (The Indian Journal of Agricultural Sciences, 2020)
Transposable elements (TEs) are a major component of the eukaryotic genomes, which are highly dynamic in nature and significantly contribute in the expansion of genome. We have genome sequence information on several legume species but there is limited information regarding the evolutionary pattern of TEs in these. To understand the expansion of the genomes, we did comparative analysis of TEs in eight different legume species, viz. Arachis durensis (Adu,2.7Gb), Arachis ipaensis (Aip,2.7Gb), Cicer arietinum (Car,738.09 Mb), Cajanus cajan (Cca,858 Mb), Glycine max (Gma,1115 Mb), Lotus japonicas (Lja,472Mb), Medicago truncatula (Mtr,465 Mb) and Vignaan gularis (Van,612 Mb). Our analysis showed that, the TEs in legume genome varied between 27.86% (Lja) to 70.62% (Aip) and LTR was the most dominant category over other TEs. Two Arachis species from Dalbergia tribe differ significantly in their total TEs content (Adu: 60.23%, Aip:70.62%). Comparative analysis indicated that despite the abundance of species-specific TEs in these genome, total 2,850 copies of repeat elements were conserved among all eight selected legume species. These belonged to LTR (n=2,514), non-LTR (n=14), and DNA transposons (n= 133). Evolutionary analysis revealed that most of the conserved TEs belonging tothe same tribe were clustered together, indicating introgression of repeats via horizontal transfer process. Intra and inter tribe divergence time analysis of conserved TEs provided evidence of single and multiple duplication events in the eight legume species.